Wind power coating as well as preparation method and application thereof

By using specific ratio composite oxides and combined curing agents in wind power coatings, the problem of insufficient corrosion resistance of existing wind power coatings in marine environments is solved, and the coatings are achieved with high adhesion, impact resistance and durability, ensuring the safety and long-term use of wind power equipment.

CN119662094AActive Publication Date: 2025-03-21HEBEI GUANGXING SEMICON TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411986120.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The corrosion resistance, adhesion and weather resistance of existing wind power coatings are not ideal in extreme marine environments, resulting in the widespread aging, peeling and rust coatings, affecting the aesthetics and service life of the equipment, and may lead to safety hazards.

Method used

A wind power coating is provided, and its composition includes resin, sheet zinc powder, composite oxide and additives. The content of Ce3+ in the composite oxide is controlled at 25-35% by weight of the total cerium element content, and a combination of anhydride curing agent and cationic curing agent is used to improve the durability and stability of the coating.

Benefits of technology

This wind power coating has the advantages of short drying time, strong adhesion, strong impact resistance, strong salt spray resistance, low corrosion current density and high corrosion potential, which significantly improves durability and safety in offshore wind power environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223524580000131
    Figure BDA0005223524580000131
Patent Text Reader

Abstract

The invention relates to a coating for wind power and a preparation method and application thereof.The coating for wind power comprises a component A and a component B. The component A comprises resin, flaky zinc powder, composite oxide and auxiliaries, the composite oxide comprises rod-like titanium dioxide and cerium oxide, and the auxiliaries comprise titanium dioxide and cerium oxide. The content of Ce < 3 + > in the composite oxide accounts for 25-35 wt% of the total content of the cerium element; and the component B is a curing agent. The wind power coating disclosed by the invention has the advantages of short drying time, strong adhesive force, strong impact resistance, strong salt fog resistance, good corrosion resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of wind power, and in particular to a wind power coating and a preparation method and application thereof. Background Art

[0002] Wind power coating is a special coating used for surface coating of wind power equipment (such as wind power blades, wind power towers, etc.). With the continuous development of wind power technology and the increasing requirements for environmental protection, the wind power coating industry is developing towards high performance, environmental protection, intelligence and multi-functionality, and continuously improving the performance indicators of coatings such as weather resistance, corrosion resistance and wear resistance; using more environmentally friendly raw materials and production processes to reduce the impact on the environment; applying intelligent technology to the research and development and production process of coatings to improve the quality and production efficiency of coatings; developing coating products with multiple functions, such as fire prevention, heat insulation, noise reduction, etc., to meet the diversified needs of wind power equipment.

[0003] Although there are many anti-corrosion coatings in use in the current market, the corrosion resistance, adhesion and weather resistance of most coatings in extreme marine environments are still not ideal. Especially after long-term use, coating aging, peeling and rusting are common. These problems not only affect the appearance and service life of the equipment, but may also cause safety hazards. Therefore, the development of a special offshore wind power coating with excellent heavy-duty anti-corrosion performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the defects existing in the prior art, the purpose of the present invention is to provide a wind power coating and a preparation method and application thereof. The wind power coating of the present invention has the advantages of short drying time, strong adhesion, strong impact resistance, strong salt spray resistance, low corrosion current density and high corrosion potential.

[0005] To achieve the above objectives, the first aspect of the present invention provides a wind power coating, which includes component A and component B, wherein component A includes resin, flaky zinc powder, composite oxide and additives, wherein the composite oxide includes rod-shaped titanium dioxide and cerium oxide, and Ce in the composite oxide is 3+ The content of Ce in the composite oxide is 25-35% by weight of the total cerium content; the component B is a curing agent. 3+ The content of Ce can be controlled, but not limited to, at 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt% and the like, accounting for the total cerium content. For another example, in the present invention, Ce in the composite oxide is 3+ The content of cerium can be controlled, but not limited to, at 25-35 wt %, 28-32 wt %, etc. of the total cerium content.

[0006] On the basis of the above technical solution, based on the total weight of the composite oxide, the content of rod-shaped titanium dioxide is 70-95% by weight, and the content of cerium oxide is 5-30% by weight.

[0007] Based on the above technical solution, the aspect ratio of the rod-shaped titanium dioxide is 2-10: 1. The aspect ratio of the rod-shaped titanium dioxide is, for example but not limited to, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, etc.

[0008] On the basis of the above technical solution, based on the total weight of component A, the content of resin is 20-50% by weight, the content of flaky zinc powder is 30-60% by weight, the content of composite oxide is 10-20% by weight, and the content of auxiliary agent is 10-20% by weight.

[0009] On the basis of the above technical solution, the curing agent is selected from an anhydride curing agent and / or a cationic curing agent. Preferably, the curing agent includes an anhydride curing agent and a cationic curing agent, and the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.6. The weight ratio of the anhydride curing agent to the cationic curing agent is, for example but not limited to, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6.

[0010] On the basis of the above technical solution, the acid anhydride curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride.

[0011] On the basis of the above technical solution, the cationic curing agent is selected from one or more of ammonium salts, aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aluminum complex curing agents, aromatic diazonium salts and pyridinium curing agents, such as but not limited to ammonium chloride, barium chloride, boron trifluoride ether complex, etc.

[0012] On the basis of the above technical solution, the weight ratio of component I to component II is 1:0.1-0.4, for example but not limited to 1:0.1, 1:0.2, 1:0.3, 1:0.4.

[0013] On the basis of the above technical solution, the resin is a phenolic epoxy resin and / or a hydroxyl-terminated polyurethane resin; preferably, the resin is a mixture of a phenolic epoxy resin and a hydroxyl-terminated polyurethane resin.

[0014] On the basis of the above technical solution, the weight ratio of the phenolic epoxy resin to the hydroxyl-terminated polyurethane resin is 1:0.5-0.8.

[0015] On the basis of the above technical solution, the phenolic epoxy resin may be but is not limited to phenolic epoxy resin F51.

[0016] On the basis of the above technical solution, the auxiliary agent is selected from one or more of a dispersant, a thixotropic agent, a leveling agent, a defoaming agent, a coupling agent and an antioxidant.

[0017] On the basis of the above technical solution, the dispersant is selected from one or more of carboxylates, sulfate esters, sulfonates, quaternary ammonium salts and pyridinium salts.

[0018] On the basis of the above technical solution, the thixotropic agent is selected from organic bentonite and / or hydrogenated castor oil.

[0019] On the basis of the above technical solution, the leveling agent is selected from one or more of BYK-307, BYK-310, BYK-320 and BYK-333.

[0020] On the basis of the above technical solution, the defoaming agent is selected from BYK-072 and / or BYK-141.

[0021] Based on the above technical solution, the antioxidant is selected from antioxidant 168 and / or antioxidant 1010.

[0022] On the basis of the above technical solution, the coupling agent is selected from silane coupling agent.

[0023] The second aspect of the present invention provides a method for preparing the above-mentioned wind power coating, comprising:

[0024] Step 1, dispersing rod-shaped titanium dioxide and cerium-containing soluble salt in a solvent, adding a precipitant and mixing, and then sequentially refluxing, cooling, drying and calcining to obtain a composite oxide; wherein Ce in the composite oxide is 3+ The content of cerium accounts for 25-35% by weight of the total cerium content;

[0025] Step 2, mixing the resin, flaky zinc powder, composite oxide and additives to obtain component A;

[0026] Step 3: Mix component B with component A; wherein component B is a curing agent.

[0027] On the basis of the above technical solution, the soluble salt containing cerium may be but is not limited to cerium nitrate, cerium sulfate and the like.

[0028] On the basis of the above technical solution, the solvent may be but is not limited to methanol, ethanol, water, etc.

[0029] On the basis of the above technical solution, the precipitant may be but is not limited to urea.

[0030] On the basis of the above technical solution, the reflux conditions include but are not limited to: temperature of 80-100° C. and time of 4-8 h.

[0031] Based on the above technical solution, the cooling conditions include: cooling to 20-25°C.

[0032] On the basis of the above technical solution, the drying conditions include but are not limited to: temperature of 100-120°C and time of 4-8h.

[0033] On the basis of the above technical solution, the calcination conditions include but are not limited to: temperature of 400-600° C. and time of 2-6 hours.

[0034] On the basis of the above technical solution, based on the total weight of the composite oxide, the content of rod-shaped titanium dioxide is 70-95% by weight, and the content of cerium oxide is 5-30% by weight.

[0035] Based on the above technical solution, the aspect ratio of the rod-shaped titanium dioxide is 2-10: 1. The aspect ratio of the rod-shaped titanium dioxide is, for example but not limited to, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, etc.

[0036] On the basis of the above technical solution, based on the total weight of component A, the content of resin is 20-50% by weight, the content of flaky zinc powder is 30-60% by weight, the content of composite oxide is 10-20% by weight, and the content of auxiliary agent is 10-20% by weight.

[0037] On the basis of the above technical solution, the curing agent is selected from an anhydride curing agent and / or a cationic curing agent. Preferably, the curing agent includes an anhydride curing agent and a cationic curing agent, and the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.6. The weight ratio of the anhydride curing agent to the cationic curing agent is, for example but not limited to, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6.

[0038] On the basis of the above technical solution, the acid anhydride curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride.

[0039] On the basis of the above technical solution, the cationic curing agent is selected from one or more of ammonium salts, aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aluminum complex curing agents, aromatic diazonium salts and pyridinium curing agents, such as but not limited to ammonium chloride, barium chloride, boron trifluoride ether complex, etc.

[0040] On the basis of the above technical solution, the weight ratio of component I to component II is 1:0.1-0.4, for example but not limited to 1:0.1, 1:0.2, 1:0.3, 1:0.4.

[0041] On the basis of the above technical solution, the resin is a phenolic epoxy resin and / or a hydroxyl-terminated polyurethane resin; preferably, the resin is a mixture of a phenolic epoxy resin and a hydroxyl-terminated polyurethane resin.

[0042] On the basis of the above technical solution, the weight ratio of the phenolic epoxy resin to the hydroxyl-terminated polyurethane resin is 1:0.5-0.8.

[0043] On the basis of the above technical solution, the phenolic epoxy resin may be but is not limited to phenolic epoxy resin F51.

[0044] On the basis of the above technical solution, the auxiliary agent is selected from one or more of a dispersant, a thixotropic agent, a leveling agent, a defoaming agent, a coupling agent and an antioxidant.

[0045] On the basis of the above technical solution, the dispersant is selected from one or more of carboxylates, sulfate esters, sulfonates, quaternary ammonium salts and pyridinium salts.

[0046] On the basis of the above technical solution, the thixotropic agent is selected from organic bentonite and / or hydrogenated castor oil.

[0047] On the basis of the above technical solution, the leveling agent is selected from one or more of BYK-307, BYK-310, BYK-320 and BYK-333.

[0048] On the basis of the above technical solution, the defoaming agent is selected from BYK-072 and / or BYK-141.

[0049] Based on the above technical solution, the antioxidant is selected from antioxidant 168 and / or antioxidant 1010.

[0050] On the basis of the above technical solution, the coupling agent is selected from silane coupling agent.

[0051] The third aspect of the present invention provides the application of the above-mentioned wind power coating in the field of offshore wind power.

[0052] Beneficial effects of the present invention:

[0053] (1) In the present invention, Ce in the composite oxide 3+ When the content is controlled within the range of 25-35 weight % of the total cerium content, it is more conducive to preventing the damage of salt water to the coating. When applied to offshore wind power, it is more conducive to the durability of the coating.

[0054] (2) The crosslinking density of epoxy resin directly affects its physical and chemical properties, including hardness, strength, heat resistance and solvent resistance. High crosslinking density usually means better mechanical properties and thermal stability, but it may also cause the material to become brittle, which is particularly evident under extreme conditions such as cold and heat shock. The present invention introduces multi-functional polyurethane segments to balance the brittleness of epoxy resin through the flexibility of the polyurethane segments while maintaining sufficient crosslinking network density. The polyurethane segments themselves have good flexibility and elasticity, and can absorb and disperse energy when the epoxy resin is impacted by external forces, thereby effectively preventing the material from cracking or breaking. This toughening effect enables the modified epoxy resin to exhibit better durability and stability in harsh environments such as cold and heat, thereby improving the overall performance of the material.

[0055] (3) Anhydride curing agents are organic substances containing acid, and their acidity comes from the anhydride groups in their molecular structure. They can react with substances containing hydrogen atoms to initiate a curing reaction and form a strong and durable solid. Anhydride curing agents usually have low volatility and high activity. Coatings cured with anhydride curing agents usually have good weather resistance and chemical corrosion resistance, and can adapt to the complex weather conditions and chemical corrosion in the offshore wind power environment. Cationic curing agents are a new type of coating curing agent with the characteristics of high strength, high hardness, wear resistance, chemical corrosion resistance and excellent weather resistance. They are new high-tech products in the coating field. The use of anhydride curing agents and cationic curing agents to cure epoxy resins has unexpectedly improved their moisture and heat resistance. This is because anhydride curing agents cure epoxy resins according to a step-by-step polymerization mechanism, while cationic curing agents cure epoxy resins according to a chain polymerization mechanism. The combination of the two can form a more stable and heat-resistant coating structure. The offshore wind power environment is complex and changeable, and the performance requirements of the coatings are high. The combined use of anhydride curing agent and cationic curing agent can improve the comprehensive performance of the coating and make it better adapted to the offshore wind power environment. However, the curing speeds of anhydride curing agent and cationic curing agent are different, so it is necessary to adjust the dosage ratio of the two. Prevent excessive use of a single component, resulting in degradation of epoxy resin performance. The ratio of the present invention, combined with other substances, can obtain a coating for offshore wind power with better performance. DETAILED DESCRIPTION

[0056] In the following technical description, for the sake of convenience of explanation, many details are provided to provide a full understanding of the disclosed embodiments. However, one or more embodiments can still be implemented without these details.

[0057] The terms "first", "second", etc. in the description and claims of the disclosed embodiments are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way are interchangeable where appropriate, so that the embodiments of the disclosed embodiments described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0058] The following are examples.

[0059] In the following examples, the raw materials were all purchased from commercial sources.

[0060] Preparation Example 1

[0061] Preparation of hydroxyl-terminated polyurethane resin:

[0062] 1000 parts by weight of dehydrated polytetrahydrofuran diol and 1 part by weight of dibutyltin dilaurate catalyst are added into the reactor, stirred and mixed, and nitrogen is introduced into the reactor for protection; the temperature is raised to 65°C, and 100 parts by weight of hexamethylene diisocyanate polyisocyanate is added, and the addition is controlled to be completed within 2 hours, and the temperature does not exceed 90°C; after the addition is completed, the internal temperature is maintained at 80-890°C for reaction for 3 hours; finally, a sample is taken, and the 8NCO content is titrated by di-n-butylamine method. When the test result is 0, a hydroxyl-terminated polyurethane resin is obtained.

[0063] Example 1

[0064] Preparation of a coating for wind power:

[0065] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;

[0066] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0067] Step 3: Mix 35 g of flaky zinc powder, 15 g of composite oxide (obtained in step 1), 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0068] Step 4: Mix 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component B.

[0069] Step 5: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0070] Example 2

[0071] A coating for wind power generation is prepared according to the method of Example 1, except that the composite oxide is different, namely:

[0072] Step 1: Take 21 g of Ce(NO3)3·6H2O and 100 g of rod-shaped rutile (aspect ratio 8:1) and add them to 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;

[0073] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 28% by weight of the total cerium content;

[0074] Step 3: Mix 35 g of flaky zinc powder, 15 g of composite oxide, 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0075] Step 4: Mix 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component B.

[0076] Step 5: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0077] Example 3

[0078] A coating for wind power generation was prepared according to the method of Example 1, except that component A was different, namely:

[0079] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;

[0080] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0081] Step 3: Mix 30 g of flaky zinc powder, 20 g of composite oxide, 25 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0082] Step 4: Mix 100 g of hexahydrophthalic anhydride curing agent and 20 g of boron trifluoride ether complex to obtain component B.

[0083] Step 5: Mix 100 g of component A with 40 g of component B to obtain a coating for wind power generation.

[0084] Example 4

[0085] A coating for wind power generation was prepared according to the method of Example 1, except that component A was different, namely:

[0086] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;

[0087] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0088] Step 3: Mix 40 g of flaky zinc powder, 10 g of composite oxide, 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0089] Step 4: Mix 100 g of hexahydrophthalic anhydride curing agent and 60 g of boron trifluoride ether complex to obtain component B.

[0090] Step 5: Mix 100 g of component A with 10 g of component B to obtain a coating for wind power generation.

[0091] Example 5

[0092] A coating for wind power generation was prepared according to the method of Example 1, except that component A was different, namely:

[0093] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;

[0094] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0095] Step 3: Mix 30 g of flaky zinc powder, 30 g of composite oxide, 15 g of phenolic epoxy resin F51, 10 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0096] Step 4: Mix 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component B.

[0097] Step 5: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0098] Example 6

[0099] A coating for wind power generation was prepared according to the method of Example 1, except that component A was different, namely:

[0100] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;

[0101] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0102] Step 3: Mix 45 g of flaky zinc powder, 5 g of composite oxide, 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0103] Step 4: Mix 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component B.

[0104] Step 5: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0105] Example 7

[0106] A coating for wind power generation was prepared according to the method of Example 1, except that component B was different, namely:

[0107] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;

[0108] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0109] Step 3: Mix 35 g of flaky zinc powder, 15 g of composite oxide, 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0110] Step 4: Mix 100 g of hexahydrophthalic anhydride curing agent and 100 g of boron trifluoride ether complex to obtain component B.

[0111] Step 5: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0112] Comparative Example 1

[0113] A coating for wind power generation was prepared according to the method of Example 1, except that the composite oxide was replaced by flaky zinc powder, that is:

[0114] Step 1: 50 g of flaky zinc powder, 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent are mixed to obtain component A.

[0115] Step 2: Mix 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component B.

[0116] Step 3: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0117] Comparative Example 2

[0118] A coating for wind power generation was prepared according to the method of Example 1, except that the hydroxyl-terminated polyurethane resin was replaced by phenolic epoxy resin F51, namely:

[0119] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;

[0120] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0121] Step 3: Mix 35 g of flaky zinc powder, 15 g of composite oxide, 35 g of phenolic epoxy resin F51, 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0122] Step 4: Mix 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component B.

[0123] Step 5: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0124] Comparative Example 3

[0125] A coating for wind power generation was prepared according to the method of Example 1, except that the boron trifluoride ether complex was replaced with a hexahydrophthalic anhydride curing agent, namely:

[0126] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;

[0127] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0128] Step 3: Mix 35 g of flaky zinc powder, 15 g of composite oxide, 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0129] Step 4: Use 100 g of hexahydrophthalic anhydride curing agent as component B.

[0130] Step 5: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0131] Comparative Example 4

[0132] A coating for wind power generation was prepared according to the method of Example 1, except that the hexahydrophthalic anhydride curing agent was replaced with a boron trifluoride ether complex, namely:

[0133] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;

[0134] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;

[0135] Step 3: Mix 35 g of flaky zinc powder, 15 g of composite oxide, 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent to obtain component A.

[0136] Step 4: Use 100 g of boron trifluoride ether complex as component B.

[0137] Step 5: Mix 100 g of component A with 30 g of component B to obtain a coating for wind power generation.

[0138] Comparative Example 5

[0139] A coating for wind power generation was prepared according to the method of Example 1, except that only Ce(NO3)3·6H2O was mixed with rod-shaped rutile:

[0140] Step 1, 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1) were mixed to obtain a mixture;

[0141] Step 2: 35 g of flaky zinc powder, 15 g of the mixture obtained in step 1, 20 g of phenolic epoxy resin F51, 15 g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), 4 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 3 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, and 2 g of Y200 fumed silica coupling agent are mixed to obtain component A.

[0142] Step 3: Mix 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component B.

[0143] Step 4: Mix 100 g of component A with 30 g of component B to obtain a wind power coating.

[0144] Test Case

[0145] The performance tests of the wind power coatings of Examples 1-7 and Comparative Examples 1-5 were respectively conducted to test drying time, adhesion, impact resistance, salt spray resistance, corrosion current density and corrosion potential. The results are shown in Table 1.

[0146] (1) Drying time is tested according to GB / T 1728-2020 at a test temperature of 23±2℃.

[0147] (2) Adhesion was tested according to GB / T 5210-2006.

[0148] (3) Impact resistance is tested according to GB / T 1732-2020.

[0149] (4) Salt spray resistance is tested according to GB / T 1771-2007.

[0150] (5) Test method for corrosion current density and corrosion potential: The electrochemical properties of the coating were analyzed using an RST-3000 electrochemical workstation, with the coating obtained in the example or comparative example as the working electrode, a saturated calomel electrode as the reference electrode, Pt as the counter electrode, and a 3.5% NaCl solution as the medium.

[0151] Table 1

[0152]

[0153] It can be seen from the above table that the wind power coating prepared by the formula of the present invention has the advantages of short drying time, strong adhesion, strong impact resistance, strong salt spray resistance, low corrosion current density and high corrosion potential.

[0154] The present application is not limited to the embodiments described above, and various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.

[0155] In the present application, each embodiment may focus on the differences from other embodiments, and the same or similar parts between the embodiments may refer to each other.

Claims

1. A coating for wind power generation, comprising component A and component B, wherein: The component A comprises resin, flaky zinc powder, composite oxide and additives, wherein the composite oxide comprises rod-shaped titanium dioxide and cerium oxide, and Ce in the composite oxide is 3+ The content of cerium accounts for 25-35% by weight of the total cerium content; the component B is a curing agent.

2. The wind power coating according to claim 1, characterized in that: Based on the total weight of the composite oxide, the content of the rod-shaped titanium dioxide is 70-95% by weight, and the content of the cerium oxide is 5-30% by weight; and / or the aspect ratio of the rod-shaped titanium dioxide is 2-10:

1.

3. The wind power coating according to claim 1 or 2, characterized in that: Based on the total weight of component A, the content of the resin is 20-50% by weight, the content of the flaky zinc powder is 30-60% by weight, the content of the composite oxide is 10-20% by weight, and the content of the auxiliary agent is 10-20% by weight.

4. The wind power coating according to any one of claims 1 to 3, characterized in that: The curing agent is selected from an anhydride curing agent and / or a cationic curing agent; more preferably, the curing agent is selected from an anhydride curing agent and a cationic curing agent, and the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.6; More preferably, the anhydride curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride; More preferably, the cationic curing agent is selected from one or more of aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aluminum complex curing agents, aromatic diazonium salts, pyridinium curing agents and boron trifluoride complexes.

5. The wind power coating according to any one of claims 1 to 4, characterized in that: The weight ratio of component A to component B is 1:0.1-0.

4.

6. The wind power coating according to any one of claims 1 to 5, characterized in that: The resin is a phenolic epoxy resin and / or a hydroxyl-terminated polyurethane resin; preferably, the resin is a mixture of a phenolic epoxy resin and a hydroxyl-terminated polyurethane resin, and more preferably, the weight ratio of the phenolic epoxy resin to the hydroxyl-terminated polyurethane resin is 1:0.5-0.

8.

7. The wind power coating according to any one of claims 1 to 6, characterized in that: The auxiliary agent is selected from one or more of a dispersant, a thixotropic agent, a leveling agent, a defoaming agent, a coupling agent and an antioxidant; Preferably, the dispersant is selected from one or more of carboxylates, sulfates, sulfonates, quaternary ammonium salts and pyridinium salts; Preferably, the thixotropic agent is selected from organobentonite and / or hydrogenated castor oil; Preferably, the leveling agent is selected from one or more of BYK-307, BYK-310, BYK-320 and BYK-333; Preferably, the defoamer is selected from BYK-072 and / or BYK-141; Preferably, the antioxidant is selected from antioxidant 168 and / or antioxidant 1010; Preferably, the coupling agent is selected from silane coupling agents.

8. The method for preparing the wind power coating according to any one of claims 1 to 7, comprising: Step 1, dispersing rod-shaped titanium dioxide and cerium-containing soluble salt in a solvent, adding a precipitant and mixing, and then sequentially refluxing, cooling, drying and calcining to obtain a composite oxide; wherein Ce in the composite oxide is 3+ The content of cerium accounts for 25-35% by weight of the total cerium content; Step 2, mixing the resin, flaky zinc powder, composite oxide and additives to obtain component A; Step 3: Mix component B with component A; wherein component B is a curing agent.

9. The preparation method according to claim 8, characterized in that: The cerium-containing soluble salt is cerium nitrate and / or cerium sulfate; and / or the precipitant is urea; And / or, the reflux conditions include: temperature of 80-90°C, time of 4-8h; and / or, the drying conditions include: temperature of 100-120°C, time of 4-8h; and / or, the calcination conditions include: temperature of 400-600°C, time of 2-6h.

10. Use of the wind power coating according to any one of claims 1 to 6 in the field of offshore wind power.

Citation Information

Patent Citations

  • Nanometer modified high-solid polyurethane anti-corrosive paint and preparation method thereof

    CN101565589A

  • Anti-H2S anti-C02 and high-temperature-corrosion-resistant polymer coating

    CN105623474A

  • Epoxy resin composition and preparation method thereof

    CN108641066A

  • Packaging adhesive for LED, use method and application thereof

    CN111826105A

  • Graphene zinc powder anticorrosive primer for high-flash-point steel structure and preparation method of graphene zinc powder anticorrosive primer

    CN114369406A